Studi Kasus: Pemalsuan Daging Sapi dengan Daging Babi Hutan di Kota Bogor - Nida, Lailatun; Pisestyani, Herwin; Basri, Chaerul (FAKULTAS KEDOKTERAN HEWAN UNIVERSITAS NUSA CENDANA, 2020)
The adulteration of beef using wild boar meat in the city of Bogor has been a serious concern in the society. Monitoring and surveillance of beef products are needed to ensure the halal of animal products and to prevent the transmission risk of zoonotic diseases from wild boar meat to humans. The purpose of this study was to analyse the data of Dinas Pertanian Kota Bogor related to meat adulteration in 2013-2017. The case study approach was used in this research by conducting a collection of primary and secondary data. The primary data obtained from an indepth interview with the chief of veterinary public health, processing, and marketing of livestock products of Dinas Pertanian Kota Bogor. The secondary data were obtained from monitoring and surveillance report of Dinas Pertanian Kota Bogor in 2013-2017. The results showed that 7.86% (3/33 samples) of beef samples contained wild boar meat during the 2013-2017 period. The adulterated beef was found mainly from the meat kiosks in traditional markets. In conclusion, monitoring and surveillance related to meat adulteration problem is needed to be improved especially in the traditional market.